2020
DOI: 10.1021/acs.biochem.0c00441
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Enhancement of Nucleotide Excision Repair of a Bulky Guanine Lesion in a Covalently Closed Circular DNA Plasmid Relative to the Same Linearized Plasmid

Abstract: The excision of DNA lesions by human nucleotide excision repair (NER) has been extensively studied in human cell extracts. Employing DNA duplexes with fewer than 200 bp containing a single bulky, benzo­[a]­pyrene-derived guanine lesion (B­[a]­P-dG), the NER yields are typically on the order of ∼5–10%, or less. Remarkably, the NER yield is enhanced by a factor of ∼6 when the B­[a]­P-dG lesion is embedded in a covalently closed circular pUC19NN plasmid (contour length of 2686 bp) rather than in the same plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…These lesions are substrates of prokaryotic BER and NER mechanisms [ 74 ], in cell extracts from HeLa cells and human fibroblasts [ 14 , 21 ], as well as in intact HeLa cells and human fibroblasts [ 19 ]. As a positive control of NER activity, we employed the bulky 10 R -(+)- cis-anti -B[ a ]PDE- N 2 -dG adduct (abbreviated as B[ a ]P-dG), an excellent substrate of the human NER pathway [ 14 , 19 , 22 , 32 , 33 ].…”
Section: Guanine Lesions Generated By Electron Abstraction and Frementioning
confidence: 99%
See 4 more Smart Citations
“…These lesions are substrates of prokaryotic BER and NER mechanisms [ 74 ], in cell extracts from HeLa cells and human fibroblasts [ 14 , 21 ], as well as in intact HeLa cells and human fibroblasts [ 19 ]. As a positive control of NER activity, we employed the bulky 10 R -(+)- cis-anti -B[ a ]PDE- N 2 -dG adduct (abbreviated as B[ a ]P-dG), an excellent substrate of the human NER pathway [ 14 , 19 , 22 , 32 , 33 ].…”
Section: Guanine Lesions Generated By Electron Abstraction and Frementioning
confidence: 99%
“…Recently we demonstrated that the interplay of BER and NER pathways in covalently closed circular plasmids dramatically differs from that in the same, but linearized plasmids [ 21 , 22 ]. A gapped-vector technology [ 75 , 76 , 77 , 78 , 79 , 80 ] was employed for the site-specific insertion of single guanine lesions into pUC19NN plasmid molecules (contour length of 2686 bp).…”
Section: Construction Of Plasmid Substrates Harboring Single Guanimentioning
confidence: 99%
See 3 more Smart Citations